2021
DOI: 10.1136/bmjopen-2021-055160
|View full text |Cite
|
Sign up to set email alerts
|

Decade of research into the acceptability of interventions aimed at improving adolescent and youth health and social outcomes in Africa: a systematic review and evidence map

Abstract: ObjectiveInterventions aimed at improving adolescent health and social outcomes are more likely to be successful if the young people they target find them acceptable. However, no standard definitions or indicators exist to assess acceptability. Acceptability research with adolescents in low-and-middle-income countries (LMICs) is still limited and no known reviews systhesise the evidence from Africa. This paper maps and qualitatively synthesises the scope, characteristics and findings of these studies, includin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 102 publications
0
9
0
Order By: Relevance
“…Additionally, while there are studies testing the effectiveness of interventions targeting youth in low and middle-income countries, intervention acceptability studies among adolescents in LMICs, specifically in Africa, are still limited [ 27 ]. Acceptability is necessary—though not sufficient by itself—for intervention effectiveness [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, while there are studies testing the effectiveness of interventions targeting youth in low and middle-income countries, intervention acceptability studies among adolescents in LMICs, specifically in Africa, are still limited [ 27 ]. Acceptability is necessary—though not sufficient by itself—for intervention effectiveness [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intervention acceptability studies are critical because interventions have higher uptake and effectiveness if adolescents find them acceptable [ 28 , 29 ]. A recent systematic review of peer-reviewed studies (published between January 2010 and June 2020) assessing intervention acceptability with youth (aged 10–24) in Africa mainly included studies focused on HIV or sexual and reproductive health outcomes [ 27 ]. Moreover, these interventions were either single interventions or only explored the acceptability of select components of a combination intervention, leaving out the opportunity to assess the acceptability of an intervention as a package.…”
Section: Introductionmentioning
confidence: 99%
“…This feedback confirmed similar findings from our formative qualitative work as well as our model of behavior change. It also builds on a small but growing number of HIV program acceptability studies with adolescents and young adults in sub-Saharan Africa [ 29 ]. Similar to this research, we found that offering social support within a safe, stigma-free environment is highly acceptable to youth with HIV [ 14 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, acceptability of the interventions by adolescents is critical for continued success of potential interventions. 35 Using participant-centred design and direct input from adolescents early in intervention development can likely increase acceptability and improve likelihood of intervention success. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Future interventions addressing the adolescent HIV continuum of care should build on the promising results from the highlighted studies and perhaps include a combination of the most effective strategies to optimise outcomes. Additionally, acceptability of the interventions by adolescents is critical for continued success of potential interventions 35. Using participant-centred design and direct input from adolescents early in intervention development can likely increase acceptability and improve likelihood of intervention success 36…”
Section: Discussionmentioning
confidence: 99%